MoCA as a Screening Tool of Neuropsychological Deficits in Alcohol‐Dependent Patients. (2nd May 2015) - Alarcon, Régis; Nalpas, Bertrand; Pelletier, Stéphanie; Perney, Pascal
<x xml:space="preserve">Abstract</x> Background Alcoholism is known to be associated with cognitive deficits mainly concerning visuospatial capacity, executive function, memory, and attention. These impairments may affect treatment efficacy which should therefore be adapted. We evaluated the potential utility of the Montreal Cognitive Assessment (MoCA) to evaluate cognitive impairment in a large series of alcoholic patients hospitalized for withdrawal and rehabilitation. Methods Consecutive recruitment during a time period of patients admitted to an addiction treatment unit of a teaching hospital. Administration of the MoCA test on admission by trained staff members. Results A total of 166 patients aged 49.9 ± 9.2 years were included. Mean duration of administration was 20 minutes. The mean MoCA score was 23.5 ± 3.5 and 68.1% had an impaired value (<26). Age was negatively and education was positively associated with the MoCA score. Significant cognitive deficits concerned visuospatial capacity, attention, fluency, abstraction, and delayed recall. Neither age nor sex was significantly related to the MoCA score, while having a high education level (>12 years) significantly increased the likelihood of having a high MoCA score. Conclusions Owing to their severity and frequency, screening for cognitive deficits is necessary in alcoholics during rehabilitation. MoCA is an appropriate tool for this purpose.